Ethical issues in Alzheimer’s disease research involving human subjects - Davis, S. (Journal of medical ethics, 2017)
As we aggressively pursue research to cure and prevent Alzheimer’s disease, we encounter important ethical challenges. None of these challenges, if handled thoughtfully, would pose insurmountable barriers to research. But if they are ignored, they could slow the research process, alienate potential study subjects and do damage to research recruits and others. These challenges are (1) the necessity of very large cohorts of research subjects, recruited for lengthy studies, probably ending only in the subjects’ death; (2) the creation of cohorts of ’study ready' volunteers, many of whom will be competent to consent at the beginning of the process, but move into cognitive impairment later; (3) reliance on adaptive trial design, creating challenges for informed consent, equipoise and justice; (4) the use of biomarkers and predictive tests that describe risk rather than certainty, and that can threaten participants’ welfare if the information is obtained by insurance companies or long-term care providers; (5) the use of study partners that creates unique risks of harm to the relationship of subject and study partner. We need greater attention, at all levels, to these complex ethical issues. Work on these issues should be included in research plans, from the federal to the local, and should be supported through NIH in the same way that it supported work on the ethical, legal and social implications of genetic research.